2015
DOI: 10.1177/0956797615569001
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Self-Control and Unemployment Throughout the Life Span

Abstract: The capacity for self-control may underlie successful labor-force entry and job retention, particularly in times of economic uncertainty. Analyzing unemployment data from two nationally representative British cohorts (N = 16,780), we found that low self-control in childhood was associated with the emergence and persistence of unemployment across four decades. On average, a 1-SD increase in self-control was associated with a reduction in the probability of unemployment of 1.4 percentage points after adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 47 publications
4
120
0
Order By: Relevance
“…Given that unemployment can change personality (Boyce, Wood, Daly, & Sedikides, 2015), these studies cannot rule out the possibility that personality was at least partly determined by unemployment, thus explaining why the two variables are related -indeed one test of reverse causality in Viinikainen and Kokko (2012) could not rule out that unemployment in early life may have affected personality by middle age. Some studies have clarified the direction of influence by Running Head: ADOLESCENT PERSONALITY AND UNEMPLOYMENT 6 examining traits measured before the respondents accumulated substantial labor market experience; for example Daly, Delaney, Egan, and Baumeister (2015) showed that more selfcontrolled children tend to experience less unemployment as adults. Self-controlled children are thought to better internalize and comply with standards and norms for behavior in order to become more conscientious adolescents (Eisenberg, Duckworth, Spinrad, & Valiente, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Given that unemployment can change personality (Boyce, Wood, Daly, & Sedikides, 2015), these studies cannot rule out the possibility that personality was at least partly determined by unemployment, thus explaining why the two variables are related -indeed one test of reverse causality in Viinikainen and Kokko (2012) could not rule out that unemployment in early life may have affected personality by middle age. Some studies have clarified the direction of influence by Running Head: ADOLESCENT PERSONALITY AND UNEMPLOYMENT 6 examining traits measured before the respondents accumulated substantial labor market experience; for example Daly, Delaney, Egan, and Baumeister (2015) showed that more selfcontrolled children tend to experience less unemployment as adults. Self-controlled children are thought to better internalize and comply with standards and norms for behavior in order to become more conscientious adolescents (Eisenberg, Duckworth, Spinrad, & Valiente, 2014).…”
mentioning
confidence: 99%
“…Additionally, prior studies have been limited by the use of small samples or have neglected to control for important early-life predictors of future employment success (such as cognitive ability and social class at birth) which are known to correlate with personality (e.g. see Daly, Delaney, Egan, and Baumeister, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Duckworth & Seligman, 2005) and have been positively linked to later life occupational success and (e.g. Daly et al, 2015;Moffitt et al, 2011). We therefore adjusted for self-control scores derived from 11 teacher-rated items from the 'inattentive' subscale of the 53-item Child Developmental Behaviors questionnaire, taken when the child was 10 years old (see Daly et al, 2015 for a full discussion of the self-control measures in Study 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…Individual differences in general cognitive ability are formed primarily in the first decade of life, are highly stable, and prospectively predict a range of key life outcomes including criminal behavior, health, and success in finding and keeping work (e.g. Daly, Delaney, Egan, & Baumeister, 2015;Heckman, 2006;Heckman, Stixrud, & Urzua, 2006). There is also extensive evidence demonstrating that general cognitive ability predicts important facets of The Leadership Quarterly 26 (2015) [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339][340][341] occupational success including job performance (Schmidt & Hunter, 2000), mobility in the job hierarchy and remuneration (Dreher & Bretz, 1991;Judge, Higgins, Thoresen, & Barrick, 1999;Salgado & Anderson, 2002;Schmidt & Hunter, 1998).…”
Section: Introductionmentioning
confidence: 99%